2020
DOI: 10.1111/acel.13194
|View full text |Cite
|
Sign up to set email alerts
|

RTN4B‐mediated suppression of Sirtuin 2 activity ameliorates β‐amyloid pathology and cognitive impairment in Alzheimer's disease mouse model

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…Moreover, the compound AK-1, a SIRT2 inhibitor, which was administered directly into the hippocampus, protected from neurodegeneration in a Tau transgenic mouse model without affecting neurofibrillary tangles [ 77 ]. In addition, other groups showed that SIRT2 inhibition improved cognitive performance in different AD transgenic mouse models via APP amyloidogenic processing [ 78 , 79 ] and Tau and microtubule stability modulation [ 78 ]. Accordingly, its inhibition or knock-out also improved autophagy and decreased typical AD cytoskeletal pathology [ 29 ], decreased Tau phosphorylation, and increased Tau/tubulin binding, improving microtubule dynamics [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the compound AK-1, a SIRT2 inhibitor, which was administered directly into the hippocampus, protected from neurodegeneration in a Tau transgenic mouse model without affecting neurofibrillary tangles [ 77 ]. In addition, other groups showed that SIRT2 inhibition improved cognitive performance in different AD transgenic mouse models via APP amyloidogenic processing [ 78 , 79 ] and Tau and microtubule stability modulation [ 78 ]. Accordingly, its inhibition or knock-out also improved autophagy and decreased typical AD cytoskeletal pathology [ 29 ], decreased Tau phosphorylation, and increased Tau/tubulin binding, improving microtubule dynamics [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ADAM10 activation also leads to the Notch receptor cleavage, which targets the genes that are vital for memory learning and synaptic plasticity ( Costa et al, 2005 ). However, specific pharmacological SIRT2 inhibition with AK7 increased non-amylogenic APP processing by α-secretase and reduced processing by BACE1, down-regulating its expression in the hippocampus and ameliorating the AD-associated pathology in 3xTg-AD and APP/PS1 mice ( Wang Y. et al, 2020 ). Hence, SIRT1 and SIRT2 influence APP processing in opposing ways.…”
Section: Sirt1 and Sirt2 In Alzheimer’s Diseasementioning
confidence: 99%
“…3F). Previous studies using a higher and longer dosage of AK7 have linked Sirt2 inhibition with reduced levels of Aβ in AD models (38) . However, we did not find changes in the in vivo levels of Aβ42 (Supp.…”
Section: Resultsmentioning
confidence: 99%